Ca isotopic geochemistry of an Antarctic aquatic system. Issue 2 (16th January 2017) - Lyons, W. Berry; Bullen, Thomas D.; Welch, Kathleen A.
Abstract: The McMurdo Dry Valleys, Antarctica, are a polar desert ecosystem. The hydrologic system of the dry valleys is linked to climate with ephemeral streams that flow from glacial melt during the austral summer. Past climate variations have strongly influenced the closed‐basin, chemically stratified lakes on the valley floor. Results of previous work point to important roles for both in‐stream processes (e.g., mineral weathering, precipitation and dissolution of salts) and in‐lake processes (e.g., mixing with paleo‐seawater and calcite precipitation) in determining the geochemistry of these lakes. These processes have a significant influence on calcium (Ca) biogeochemistry in this aquatic ecosystem, and thus variations in Ca stable isotope compositions of the waters can aid in validating the importance of these processes. We have analyzed the Ca stable isotope compositions of streams and lakes in the McMurdo Dry Valleys. The results validate the important roles of weathering of aluminosilicate minerals and/or CaCO3 in the hyporheic zone of the streams, and mixing of lake surface water with paleo‐seawater and precipitation of Ca‐salts during cryo‐concentration events to form the deep lake waters. The lakes in the McMurdo Dry Valleys evolved following different geochemical pathways, evidenced by their unique, nonsystematic Ca isotope signatures. Key Points: Ca stable isotopes were used to validate Ca sources and processes affecting Ca in streams and lakes of the McMurdo Dry Valleys The streams and lake surface waters have similar Ca stable isotope composition indicating that the primary source of Ca 2+ is from mineral weathering The heavy Ca isotope signature in the hypolimnia of West Lake Bonney and Lake Fryxell shows evidence of Ca‐salt precipitation